Developmental Differences in Foreign Language Instruction: A Comparative Study of Child and Adult Learners - Shamsiyeva, Aziza Shuxrat qizi (The Lingua Spectrum, 2026)
This article examines the developmental, psychological, and pedagogical differences between teaching foreign languages to children, adolescents, and adults. The study explores age-related factors influencing language acquisition, including cognitive development, motivation, emotional characteristics, communicative behavior, and social interaction. Special attention is given to young learners’ ability to acquire language implicitly through play-based, interactive, and communicative activities that promote natural language use and learner engagement. The article also highlights the influence of peer relationships and friendship on motivation and communicative competence in language learning environments. In contrast, adolescent and adult learners are described as relying more heavily on explicit instruction, analytical thinking, metacognitive awareness, and goal-oriented learning strategies. Drawing on contemporary theories and research in foreign language pedagogy, the study emphasizes the necessity of applying learner-centered teaching approaches that correspond to learners’ developmental and psychological characteristics. The findings suggest that age-sensitive instructional methods significantly contribute to improving the effectiveness, motivation, and overall outcomes of foreign language education.